Implementasi Budaya Gotong Royong Melalui Projek Penguatan Profil Pancasila di SD Negeri Teguhan 2 - Kasanah, Alvi Hidayatul; Malaikosa, Yes Matheos Lasarus; Putra, Army Al Islami (Global Education Journal, 2023)
This study aims to create a picture of the situation or event, namely the culture of mutual cooperation through a project to strengthen the profile of Pancasila students with an emphasis on the habituation of students of Teguhan 2 Elementary School. This study aims to: 1) Find out what are the values ​​of the Pancasila student profile contained in the mutual cooperation learning method at Teguhan 2 Elementary School. 2) Find out the implementation of the mutual cooperation learning method in fostering characters that are in accordance with the profile of Pancasila students at Teguhan 2 Elementary School. This study uses a descriptive qualitative method, namely the researcher conducted observations, interviews, and documentation of the mutual cooperation learning activities of grade 5 students of Teguhan 2 Elementary School and the role of teachers in providing assistance to students in the mutual cooperation learning process. The data collection process was carried out using 3 techniques, namely observation, interviews, and documentation. In the data analysis activity, there are three flows, namely data condensation, data presentation, and drawing conclusions/verification. Based on the data collected by the researcher, the researcher can conclude that: 1) the mutual cooperation learning activities before the occurrence of Covid-19 at SDN Teguhan 2 were quite good in terms of social skills, development of a sense of responsibility, respect for the environment, and understanding of Pancasila values. 2) there was a significant decline during mutual cooperation learning. 3) After distance learning during Covid-19, there was an indication of students' tendency towards socializing with friends and being selective about other friends, this is not in line with the application of the Pancasila student profile. 4) the role of teachers in assisting the habituation of mutual cooperation learning, namely: a. providing education, b. supervising mutual cooperation learning activities, and c. utilizing the habituation of mutual cooperation learning.